PENGARUH KUALITAS JASA PELAYANAN TERHADAP CITRA INSTALASI RADIOLOGI DI RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Shohibul Umam; Siti Dyah Handayani; Qurratul 'Aini (Universitas Muhammadiyah Yogyakarta, 2014)
Background : RSGM-P UMY already have tools such as the installation of radiological medical support enforcement destined diagnose oral disease. Problems that arise sometimes results are not as expected , and response less in service . The purpose of this study to analyze and explain the effect of partial and simultaneous quality radiology services to the installation image in RSGM-P UMY. Method : using quantitative methods , research subjects dentists and coass student in RSGM- P UMY . Installation of radiological research object . Types of studies using cross-sectional data was obtained from questionnaires and analyzed using multiple regression. Results: The regression equation based on existing variables positively influence the assurance (0.069), empathy (0.171), reliability (0.073), responsiveness (0,037), services (0.450), professionalism (0.326) and there was a negative , namely physical appearance (-0.016). Based on the t test of the quality of service simultaneously affect the installation image RSGMP UMY , based on the F test ( Anova : Sig . 0,000 ) is the quality of service simultaneously affect the image RSGMP UMY installation , and test results influence the determination coefficient percentage at 39.5 % . Conclusion: The services quality there are assurance, empathy , reliability , responsiveness , physical appearance have partial can’t effect on image radiologi installation. Variable service and professionalism have an influence on the image of radiological installations RSGMP UMY . The variable quality services have an simultan effect on the image of radiological installations RSGMP UMY.